Pengaruh Penggunaan Multimedia Edpuzzle Terhadap Hasil Belajar Informatika Siswa Kelas X SMA Negeri 14 Maros - Isma, Nur; Nasir, Nasir; Ayu, Sadriana (LPPM Institut Pendidikan Nusantara Global, 2025)
The study aims to see if the use of multiple media edpuzzle will affect the information of 14 maros public high school x students. This type of research is quantitative research with pre-experiment design in the form of one group pretest-posttest design. The population in this study is all 4th-grade public high school x students with 140 students. The sample in this study is an x.1 state high school student with 36 students. Sampling retrieval technique using the simple random sampling. The data-collection technique used is observation, testing and documentation. The data analysis techniques used are descriptive statistical analysis techniques and inferential statistical analysis techniques consisting of normality tests, homogenity tests and hypothetical tests. Hypothetical tests using tests - t and determinative coefficiencies. Research results from descriptive statistical analysis suggest that in the initial test (pretesting) before the application of multimedia edpuzzle in the student's average value learning process was 50.28 at the low intervals of the ideal 100 score. Whereas on the final test after the application of multimedia edpuzzle in the learning process the 83.06 student average score with high intervals of the ideal 100 score. Further analysis of inferential statistics USES the test-t formula shows that value = 11.955 and value = 1.690 with a degree of significance α = 5% or 0,05 and the degree of freedom = 35. Based on the testing criteria if > then was rejected approved. After discovering which is 11.955 and 1.690, > = 11.955 > 1.690 the difference in both significant pretests and posttests and can be concluded that was rejected and was accepted. Based on the above data, it could be concluded that the use of multimedia edpuzzle affects the information of 14 maros public high school x class.